A real recycling loop of sulfur-cured rubber through transalkylation exchange of C–S bonds. Issue 24 (8th November 2018) - Tang, Zhenghai; Liu, Yingjun; Huang, Qingyi; Zhao, Jinshan; Guo, Baochun; Zhang, Liqun
Abstract : A feasible way to recycle sulfur-cured rubber by engineering transalkylation exchange of C–S bonds in the cross-linked networks is explored. Abstract : Recycling of sulfur-cured scrap rubber is of growing importance worldwide due to the scarcity of rubber resources and environmental pollution. Herein, we report a feasible way to recycle sulfur-cured rubber by utilizing transalkylation exchange of C–S bonds, which enables the cross-linked rubber network rearrangement and thus confers the materials with the ability to be reprocessed.